ANALISIS TINGKAT KESEHATAN BANK PADA PT. BPR SINDANG BINAHARTA - Paleni, Herman Paleni; Aprianto, Ronal (Universitas muhammadiyah palembang, 2018)
Health Analysis of Rural Banks (BPR) Based on the Decree of the Board ofDirectors of Bank Indonesia no. 30/12 / Kep / DIR Date 30 April 1997 onProcedures for Rating of Rural Bank Health Rating (BPR). The Health Ratingof Rural Banks (BPR) is measured using the parameters of Capital, AssetsManagement, Earning and Liguity. This study determines the healthpredicate of the bank. Data used in the form of bank financial statementspublished in 2011 - 2015. data collection techniques used financial studymethods, methods of documentation, method keperpustakaan. The capitalaspect shows PT. BPR Sindang Binaharta is able to maintain themanagement of its own capital and risky assets, and able to cover the losseson the loans. The quality aspect of productive assets shows PT. BPRSindang Binaharta is less able to overcome business risks contained in thegiven credit component. aspects of management, during the year 2011 -2015 PT. BPR Sindang Binaharta has a level of effectiveness that has notbeen well connected with the results of NPM calculation in 2015. The profitaspect shows PT. BPR Sindang Binaharta is able to bear the existingoperational expenses with received operating income. Liquidity aspectshows PT. BPR Sindang Binaharta has the ability to meet the obligationsthat must be met and can repay its depositors.